(3GdCUhd GdELQGFjI ai GdeMGceGJ GdLRGFjI GdYScQjI GdYQGbjI (B: s (3OQGSI JMdjdjI JCUjdjI ebGQfI (B/ s - (3ThGf YGQH UGObs; (3MSfjf UGdM YHjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3Cf GdeDSSI GdYScQjI WHjYJgG GdJfXjejI GdNGUI(B: (3GdJi JSJeO ef WHjYI GdhXjaI GdefGWI HgG(B: (3h bO GbJVJ gPg GdWHjYI GdJi JJejR HgG GdeDSSI GdYScQjI Cf Jchf dgG fXGegG GdNGU(B: (3h GdPi jTed LejY LhGfH GdMjGI GdYScQjI HMjK jJVef GdbhGYO GdJi JfXe Jdc GdeDSSI h GdbhGYO GdJi JMejgG h JMGaX Ydi eUGdMgG(B. (3h jdLC GdeTQY Gdi GdJTQjYGJ GdYScQjI ddJhajb Hjf eJWdHGJ GdfXGe GdYScQi h ebJVjGJ GdbGfhf(B: (3h bO GUOQ GdeTQY GdYScQi GdYQGbi bGfhf GUhd GdeMGceGJ GdLRGFjI GdYScQi Qbe (B22 (3dSfI (B2016 (3h GdPi jYed Ydi JfXje GdbVGA GdYScQi ai GdYQGb(B. (3h Cf GdHMK ai GdCUhd GdGLQGFjI ai GdeMGceGJ GdLRGFjI GdYScQjI(B. (3jSJgOa JMOjO h JfXje GdYed GdbVGFi ai GdbhGJ GdeSdMI ef NdGd JfXje h JMOjO GdLgGJ GdJi JJhdi eeGQSI GdbVGA(B: (3h UdGMjGJ cd efgG h ef Ke GdGLQGAGJ GdJi JJHY ai GdeMGceGJ GdYScQjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B438-447s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdCUhd GdELQGFjIs; (3GdbGfhf GdLfGFj GdYQGbjs; (3GdbGfhf GdYScQj GdYQGbjs; (3GdeMGceGJ GdLRGFjI GdYScQjIs; (3GdGSJOdGd GdYScQjs; (3GdVHW GdbVGFj GdYScQjs; (3GdJeGS GYGOI GdfXQs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs